El formalismo auto-dual de Araki y estados topológicos de la materia cuántica (2017)
In the present document we present the construction of alge- braical structures from a vector space with bilinear and symmetric forms, known as Clifford algebras. These algebras involve the Dirac equation as an anticommutation condition for their elements. We present the cano- nical isomoprhism with the exterior algebra of the original vector space. This isomorphism will be useful when dealing with the Fermionic Fock space.